Personality traits and career orientations of high school students when choosing a medical profession - Tsaranov, Konstantin N.; Zhiltsov , Vladimir A.; Klimova, Elena M.; Komolova, Olga O. (International Journal of Psychosocial Rehabilitation, 2020)
The authors conducted a theoretical analysis regarding the problem of professional orientation for high school students. As a result it was determined that offering a proper career orientation for students is necessary in order for their social motives to coincide with student’s abilities and received education to be implemented fully in the professional field. It was also determined that professional self-determination is affected by a number of personality subsystems such as intelligential, occupational and psychological. Intelligential subsystem includes cognitive and reflective components, occupational - professional abilities and knowledge, psychological - motivational and moral components. In this paper were introduced the results of the empirical research on personality traits and career orientation of high school students who are taking classes in a general education institution with a medical specialization. The obtained results are important for providing the professional orientation to students in high school. It was discovered that for the majority of pupils are common the following traits: • average level of interest regarding a medical career; • the most typical behaviour patterns during a conflict are cooperation and compromise; • the main career values are professional competence, a sense of duty, Discovered correlations prove the importance of the conscious choice, of being well-informed about the variety of medical positions and well-prepared to make a decision regarding one’s career path.